Perlindungan Hukum Pada Obat Tradisional di Daerah Karo Berdasarkan Prespektif Hak Kekayaan Intelektual - Oren Basta Anugerah; Budi Santoso (Notarius, 2022)
Indonesia has a rich knowledge of traditional medicine and medicinal plants amounted to approximately 9605 (Nine thousand six hundred and five) species of medicinal plants. The problems are legal protection of traditional medicines according to Intellectual Property Rights, and the role of the government in the use of traditional medicinal knowledge in the perspective of intellectual property law in Karo District. The authors used an applied normative approach. Data collection in the writing of this research was carried out by means of literature study and document study. The data obtained were managed using qualitative analysis. Based on the results of the study showed that: (1) The Legal protection of traditional medicines according to intellectual property rights includes obtaining an invention and then seeking legal protection, as well as the process of commercializing the invention until it is profitable.(2) The role of the government in the use of traditional medicinal knowledge in the perspective of intellectual property law in Karo Regency, namely: the government has a role as an institution that supports the exclusive ownership of traditional knowledge by making intellectual property the part that determines who and how people or institutions can use it.Keywords: Legal Protection; Traditional Medicine; Traditional Knowledge AbstrakIndonesia kaya akan pengetahuan obat tradisional dan tanaman obat yang berjumlah kurang lebih 9.606 (Sembilan ribu enam ratus enam) spesies tanaman obat. Permasalahan adalah perlindungan hukum terhadap obat-obatan tradisional menurut Hak Kekayaan Intelektual, dan peran pemerintah terhadap penggunaan pengetahuan obat tradisional dalam perspektif hukum kekayaan intelektual di Kabupaten Karo. Penulis menggunakan pendekatan yuridis empiris. Pengumpulan data dalam penulisan penelitian ini dilakukan dengan cara studi pustaka. Data yang diperoleh dikelola menggunakan analisis kualitatif. Berdasarkan hasil penelitian dapat diketahui bahwa: Perlindungan hukum terhadap obat-obatan tradisional menurut Hak Kekayaan Intelektual baik itu memperoleh invensi untuk kemudian dicarikan pelindungan hukumnya, serta proses komersialisasi invensi sampai dengan memperoleh keuntungan. Peran pemerintah terhadap penggunaan pengetahuan obat tradisional dalam perspektif hukum kekayaan intelektual di Kabupaten Karo yaitu: pemerintah memiliki peran sebagai lembaga yang menjadi pendukung kepemilikan eksklusif pengetahuan tradisional dengan mejadikan kekayaan intelektual sebagai bagian yang menentukan siapa dan bagaimana orang atau lembaga dapat memanfaatkannya.Kata kunci: perlindungan hukum; obat-obatan tradisional; hak kekayaan intelektual